Indolo[3, 2-b]carbazole-based poly(arylene ethynylene)s: Modulation of their optoelectronic properties by changing the position of substituents. (August 2015) - Grigoras, Mircea; Negru, Oana Iuliana; Solonaru, Ana Maria
A novel family of indolo[3, 2-b]carbazole (ICZ)-based polymers was designed and synthesized using Sonogashira cross-coupling reaction between three bis bromine indolo[3, 2-b]carbazoles and 1, 4-diethynylbenzene. The new polymers have an arylene ethynylene structure with ICZ moiety interconnected in the main chain by 2, 8-, 3, 9- or 6, 12- positions. The polymers were obtained as partially soluble materials, in chlorinated, aromatic and aprotic polar solvents. The structure of the polymers was studied by spectroscopic methods such as Fourier transform infrared, proton and carbon-13 nuclear magnetic resonance, ultraviolet–visible and photoluminescence spectroscopies, thermogravimetry and molecular weights determined by gel permeation chromatography. Electrochemical properties were investigated by cyclic voltammetry using films cast on platinum disc working electrode. Optical and electronic properties were discussed from the viewpoint of the connection positions of ICZ units in the polymer chain.